Institutionalized Organizational Learning and Strategic Renewal: The Benefits and Liabilities of Prevailing Wisdom. (November 2013) - Lengnick-Hall, Cynthia A.; Inocencio-Gray, Jessica L.
Strategic renewal depends on achieving an appropriate balance between using what an organization has learned and continuing to gain new insights and solutions. The process of institutionalizing organizational learning is at the center of this tension since it occurs at the pivot point of exploitation and exploration. We apply a dynamic perspective of Perrow's typology of work technologies to explore the relation between the number of exceptions and analyzability of the problems likely to be encountered in various work settings and institutionalized learning. We propose that the nature of what is learned and actions leading to institutionalization differ across work contexts because of the varying complexity of problems and solutions. We explore the interactions surrounding institutionalized learning, exploration, and exploitation and argue that strategic renewal is strongly influenced by the way institutionalized learning effects the dynamic tension between exploration and exploitation.